Persepsi Mahasiswa terhadap Pembelajaran Online - Nurullah Sururi Afif; Putie Maharani Basa; Anantha Zakharia (CV. Syntax Corporation Indonesia, 2021)
The world is currently being hit by thepandemic Covid-19 that is happening in all countries. Thepandemic Covid-19 has made the living arrangements of citizens undergo enormous changes, including in learning activities. particularly on learning activities carried out in Indonesia, the government has made a policy of teaching and learning online or online.related to online learning activities, research is carried out to understand the condition of students in online learning activities. This research uses a quantitative descriptive analysis procedure with a research instrument in the form of a questionnaire distributed online through the google form. This research aims to determine students' perceptions of online education at the University of Bina Sarana Informatika Kaliabang Bekasi, where they have participated in online learning throughout thepandemic Covid-19. The purpose of this study is to understand how students perceive online education during thepandemic Covid-19. 19, where in this study the sample used was 180 people. The results of descriptive analysis, it is known that the majority of students have a fairly good perception of the application of online lectures.